Cold Hardiness in Plants Molecular Genetics, Cell Biology and Physiology - Chen, T. H. H.; Fujikawa, M.; Ebooks Corporation (Wallingford : CABI, 2006)
This book is based on invited and selected offered papers-suitably revised and updated-from the 7th International Plant Cold Hardiness Seminar held at Hokkaido University, Japan, in July 2004. These papers present the latest research findings on plant freezing and chilling stress from major laboratories around the world.
Contenido: 8 Ectopic Overexpression of AtCBF1 in Potato Enhances Freezing Tolerance9 Overexpression of a Heat-inducible apx Gene Confers Chilling Tolerance to Rice Plants; 10 Physiological and Morphological Alterations Associated with Development of Freezing Tolerance in the Moss Physcomitrella patens; 11 Control of Growth and Cold Acclimation in Silver Birch; 12 The Role of the CBF-dependent Signalling Pathway i
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: PLANTAS